THE AUTHOR'S STRUGGLING VALUES IN CULTURAL REPRODUCTION NOVEL BIOGRAPHICAL NOVEL 49 HARI KISAH PENANTANG GELOMBANG BY NURIL BASRI - Nuke Affandy, Ali; Hermoyo, R. Panji; -, Suhandoko; Widyaiswara, Tiara (TELL - US JOURNAL, 2025)
The development of the era and the development of literary science make novels not only fictional. The novel 49 Hari Kisah Penantang Gelombang by Nuril Basri is written based on the reality that occurs in the real world, so it can be called a biographical novel. Starting from human existence in facing a series of extreme problems that arise in real life, then reproduced by the author into a biographical novel. The purpose of this study is to describe the author’s struggling value in writing the novel 49 Hari Kisah Penantang Gelombang. To reveal these values, the theory on the aspect of struggle values will be utilized. The research method used is descriptive qualitative, with Abrams' expressive criticism approach to the sociology of the author. The data collection technique used is documentation study. While the data analysis technique is qualitative data analysis. The results of the study show the values of struggle: persistence, patience, never giving up, and the responsibility of a novelist in conducting research to reproduce true stories into literary works in the biographical novel genre.